Pengembangan Serious Game Menggunakan DPE Framework untuk Mengasah Kemampuan Berhitung dengan Gestur Tangan - Aditya Luthfi Alvari Ramadhan; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Counting has been a basic need in daily life activities such as trading, working, studying, etc. The ability to count can decline over time if not trained regularly. This causes a decline in counting ability. One of the effective methods to enhance counting skills is by using hand gestures as hand gestures can reduce cognitive load. In order to make the learning process with hand gestures fun, games can be used as a media for learning. Games are known to be able to make players feel happy, reduce stress, and improve their logic. Based on that premise, a serious game is developed using hand gestures as input method to enhance counting skills. To design a beneficial and fun serious game, the design process is aided by Design, Play, Experience Framework or commonly known as DPE Framework. The usage of this framework will hopefully increase the chance of success in the learning process without sacrificing the fun factor of the serious game design. In order to measure the experience performance of the game, two types of testing are used in this research such as Play Testing and Game Experience Questionnaire (GEQ). Test results from 33 respondents showed that the game is fun and beneficial with low levels of negative experience, tiredness, and disorientation. Overall, players found the game fun with a rating of 4,12 out of 5.